The anti-diabetic potentials of methanolic extract of Ficus mollis leaves in alloxan induced diabetic rats - Ravichandra V.D,; Padmaa M Paarakh, (International Journal of Phytomedicine, 2014)
Objective: The present study was designed to evaluate the acute and chronic effects of the extract against alloxan induced diabetic rats. Methods: In acute study, hypoglycemic potency of methanolic extract of Ficus mollis was assessed by oral glucose tolerance test (OGTT) and in chronic study of 21 days, extract at different doses ( ie 100, 200 and 400mg/kg) was screened for its anti-diabetic activity. Blood glucose level had been estimated at 1st, 7th, 14th and 21st and addition to this serum concentrations of insulin, triglycerides, cholesterol, SGOT, SGPT and urea determined at 21st day of the study. Results: In OGTT, standard glibenclamide and extract (200 and 400mg/kg) have shown significant reduction in blood glucose level compared to control group. In chronic model the methanolic extract was more effective in reducing the blood glucose levels (P<0.001) and effect was comparable to that of standard. The extract could also significantly (P<0.001) reduce concentrations of SGOT, triglycerides, cholesterol and urea in serum and significantly (P<0.001) increased the insulin level in blood which proves beneficial effects of the extract in diabetes. The change in concentrations of SGPT and urea were less significant (P>0.01). Conclusion: The methanolic extract of Ficus mollis posses significant antidiabetic activity in alloxan induced diabetic animal model.